Match fatigue time-course assessment over four days: Usefulness of the hooper index and heart rate variability in professional soccer players - Rabbani, A.; Clemente, F. M.; Kargarfard, M.; Chamari, K. (Frontiers in Physiology, 2019)
The aims of the present study were to (a) examine recovery time-course and (b) analyze the usefulness of the Hooper-Index (wellness index) and resting heart rate variability (HRV) in professional soccer players during an in-season phase. The Hooper-Index and resting HRV were collected on matchday and on the four following days in three consecutive in-season weeks in nine players (25.2 ± 4.3-years). The usefulness of monitoring variables was assessed by (a) comparing noise (typical error, TE) to the smallest worthwhile change (SWC) (TE/SWC) and (b) comparing match-related changes (i.e., signal) to TE (i.e., signal-to-noise ratio). Between-days standardized differences in the changes of Hooper-Index and HRV were compared to the SWC using magnitude-based inferences. The magnitudes of TE were small and moderate for the Hooper-Index and HRV, respectively. The Hooper-Index showed to be more useful than HRV for monitoring match-induced fatigue as having a lower TE/SWC (3.1 versus 4.4) and a higher signal-to-noise ratio (5.5 versus 1.5). Small-to-very large [range of effect sizes, 0.48; 2.43, confidence limits (0.22; 2.91)] and moderate-to-large [-1.71; -0.61 (-2.44; -0.03)] detrimental changes in Hooper-Index and HRV, respectively, were observed on the days following matchday. While group analyses showed a similar pattern for recovery time-course, more individual players responded, similarly when tracked using the Hooper -Index compared to when they were tracked using HRV. An inverse moderate within-individual relationship was observed between changes in the Hooper index and HRV [r = -0.41, (-0.60, 0.18)]. The Hooper index is an easy-to-use, no-cost, and non-invasive monitoring tool and seems promising for tracking match-induced fatigue during in the season in professional soccer.